The Causal and Force Perception and Their Perceived Asymmetries in Flight Collisions - Wang, Yuying (Front Psychol, 2020)
The present study was to investigate causal perception and force perception in ecological objects. Four experiments were designed to compare the perceived causality and force of one of the two objects on the other by changing the property of one or both of the objects involved in the launching effect. Our results support causal asymmetry and force asymmetry, in which the launcher has a greater causal effect and exerts more force on the target. Furthermore, we also found that, the ecological object, which is the airplane in this study, had a greater causal effect and exerted more force, resulting in strengthened asymmetries when the airplane acted as the launcher and weakened asymmetries when the airplane acted as the target. The properties of the object also impacted causal perception by attenuating the effect of the temporal gap on causality. Those results indicate that the airplane is perceived as the main cause for a collision compared with an abstract object. The influence of conceptual knowledge of the object and the sense of agency on changing the degree of perceived causality and force in a particular motion pattern was discussed.